A high-entropy manganese iron lithium phosphate composite positive electrode material, a preparation method thereof, an electrode sheet, and a battery
Patent Information
- Application Number
- CN202611131751.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-29
AI Technical Summary
[0002]磷酸锰铁锂是在磷酸铁锂中掺杂锰元素形成的新型正极材料,由于锰元素具有提升电压平台的作用,使得磷酸锰铁锂具备更高的能量密度;然而,锰铁互溶后易导致晶体结构发生畸变,且电池循环过程中还可能发生锰溶出与电解液发生反应,从而导致磷酸锰铁锂的循环稳定性和倍率性能较差,难以满足高能量密度动力电池的需求
本发明先以铁源溶液、锰源溶液和磷源溶液,经第一次液相沉淀构建磷酸盐前驱体骨架,再将其分散于分散剂溶液中,而后与磷源溶液和掺杂元素源溶液混合进行第二次液相沉淀,使得多种掺杂元素源沉淀在磷酸盐前驱体骨架表面形成高熵化合物包覆层,不仅可以促进掺杂元素在原子尺度上均匀分布于磷酸盐前驱体骨架表面,还能避免多种异类金属离子的溶度积不同而造成成分偏析。同时,第一段烧结去除原料中的结晶水、有机物和其他挥发性组分,并让部分有机物初步分解产气,利用气体排出形成多孔骨架,增加反应面积,为后续掺杂元素的充分扩散提供通道;第二段烧结主要是温度升高加速化学反应进行,晶粒发生重结晶并逐渐长大形成橄榄石晶体结构,为多种掺杂元素提供关键的能量和扩散时间,使其能均匀嵌入晶格,实现高熵结构的原子级均化。第三段烧结主要是提高结晶度,修复晶体内部缺陷,提高材料的本征稳定性,且此时碳源完全碳化,在颗粒表面形成均匀的纳米碳层,构建导电网络以弥补材料本征导电性差的缺陷,并作为物理屏障抑制副反应。通过两次液相沉淀与三段梯度烧结相结合,赋予高熵磷酸锰铁锂复合正极材料良好的循环稳定性和优异的倍率性能。
Smart Images

Figure CN122627403B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of methods or apparatus for directly converting chemical energy into electrical energy, and particularly to a high-entropy lithium manganese iron phosphate composite cathode material, its preparation method, electrode sheet, and battery. Background Technology
[0002] Lithium manganese iron phosphate (LMP) is a novel cathode material formed by doping lithium iron phosphate with manganese. Since manganese can improve the voltage platform, LMP has a higher energy density. However, the mutual solubility of manganese and iron can easily lead to distortion of the crystal structure, and manganese may also dissolve and react with the electrolyte during battery cycling. As a result, LMP has poor cycle stability and rate performance, making it difficult to meet the requirements of high energy density power batteries. Summary of the Invention
[0003] The purpose of this invention is to overcome the shortcomings of the prior art and provide a high-entropy lithium manganese iron phosphate composite cathode material, its preparation method, electrode sheet, and battery.
[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a method for preparing a high-entropy lithium manganese iron phosphate composite cathode material, comprising the following steps: S1. Mix the iron salt solution, manganese salt solution and phosphorus source solution, carry out the first co-precipitation reaction, age and dry to obtain phosphate precursor A; S2. Mix the phosphate precursor A, dispersant solution, phosphorus source solution and dopant element source solution described in S1, and carry out a second co-precipitation reaction to obtain phosphate precursor B. S3. The phosphate precursor B, lithium source, carbon source, ion-conducting agent and polar organic solvent solution described in S2 are mixed and dried. The dried product is then subjected to first-stage sintering, second-stage sintering and third-stage sintering in an inert gas atmosphere to obtain a high-entropy lithium manganese iron phosphate composite cathode material. The doping element source solution in step S2 contains three or more doping elements; In step S3, the sintering temperature of the first stage is T1, the sintering temperature of the second stage is T2, and the sintering temperature of the third stage is T3. T1, T2, and T3 satisfy: T1 < T2 < T3.
[0005] This invention first constructs a phosphate precursor framework using iron, manganese, and phosphorus source solutions through a first liquid-phase precipitation process. This framework is then dispersed in a dispersant solution and mixed with the phosphorus and dopant source solutions for a second liquid-phase precipitation. This process allows multiple dopant sources to precipitate on the surface of the phosphate precursor framework, forming a high-entropy compound coating layer. This not only promotes the uniform distribution of dopant elements on the surface of the phosphate precursor framework at the atomic scale but also avoids compositional segregation caused by different solubility products of various dissimilar metal ions. Simultaneously, the first sintering stage removes water of crystallization, organic matter, and other volatile components from the raw materials, and allows some organic matter to initially decompose and generate gas. The gas is then released to form a porous framework, increasing the reaction area and providing channels for the full diffusion of subsequent dopant elements. The second sintering stage primarily involves increasing the temperature to accelerate the chemical reaction, causing the grains to recrystallize and gradually grow into an olivine crystal structure. This provides crucial energy and diffusion time for the various dopant elements, enabling them to uniformly embed into the crystal lattice and achieving atomic-level homogenization of the high-entropy structure. The third stage of sintering primarily improves crystallinity, repairs internal crystal defects, and enhances the intrinsic stability of the material. At this stage, the carbon source is fully carbonized, forming a uniform nano-carbon layer on the particle surface. This layer constructs a conductive network to compensate for the material's poor intrinsic conductivity and acts as a physical barrier to suppress side reactions. By combining two liquid-phase precipitation stages with three-stage gradient sintering, the high-entropy lithium manganese iron phosphate composite cathode material is endowed with excellent cycle stability and superior rate performance.
[0006] The dispersant in step S2 can better inhibit the agglomeration of phosphate precursor A particles, thereby improving the uniformity of liquid phase precipitation coating; the polar organic solution in step S3 can effectively promote the preferential growth of lithium manganese iron phosphate crystals and shorten the lithium ion diffusion path; the dual coating of carbon source and ion-conducting agent can reduce the ion migration resistance at the interface, thereby improving the overall ionic conductivity of the high-entropy lithium manganese iron phosphate composite cathode material and improving its rate performance.
[0007] In some embodiments, step S1 specifically includes the following steps: adding manganese salt solution, phosphorus source solution and alkaline solution to the reaction vessel in parallel flow, while continuously adding iron salt solution to the manganese salt solution, so that the molar ratio of manganese to iron in the manganese-iron mixed solution entering the reaction vessel gradually changes from 1:0 to 0:1, to carry out the first co-precipitation reaction, and aging and drying after the reaction is completed to obtain phosphate precursor A; along the direction from the center to the surface of the phosphate precursor A, the molar content of manganese decreases in a gradient and the molar content of iron increases in a gradient.
[0008] In some embodiments, the dopant elements in the dopant source solution in step S2 include at least three of the following: Mg, Al, Ca, Ti, V, Cr, Ni, Co, Cu, Zn, Zr, Nb, Mo, Sn, Ta, W, Sb, and La.
[0009] In some embodiments, the iron salt in the iron salt solution is a soluble divalent iron salt.
[0010] In some embodiments, the concentration of the iron salt solution is preferably from 0.01 mol / L to 10 mol / L, more preferably from 1 mol / L to 6 mol / L, for example, but not limited to any or both of the following values: 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, and 10 mol / L.
[0011] In some embodiments, the manganese salt in the manganese salt solution is a soluble manganese salt.
[0012] In some embodiments, the concentration of the manganese salt solution is preferably from 0.01 mol / L to 10 mol / L, more preferably from 1 mol / L to 6 mol / L, for example, but not limited to any or both of the following values: 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, and 10 mol / L.
[0013] In some embodiments, the phosphorus source in the phosphorus source solution is preferably at least one of phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, and disodium hydrogen phosphate.
[0014] In some embodiments, the concentration of the phosphorus source solution is preferably from 0.01 mol / L to 10 mol / L, more preferably from 1 mol / L to 6 mol / L, for example, but not limited to any or both of the following values: 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, and 10 mol / L.
[0015] In some embodiments, the dispersant in the dispersant solution is preferably at least one of polyammonium compounds, phosphate ester compounds, quaternary ammonium salts, maleic anhydride polymers, carboxylic acid compounds, cationic acrylate polymers, polyethyleneimine derivatives, polyacrylamide, amphoteric polyacrylamide, polyacrylates, and polypropylene glycol-type polyols.
[0016] In some embodiments, the concentration of the dispersant solution is preferably from 0.01 mol / L to 15 mol / L, more preferably from 0.5 mol / L to 3 mol / L, for example, but not limited to any or both of the following values: 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L, 12 mol / L, 13 mol / L, 14 mol / L, and 15 mol / L.
[0017] In some embodiments, the concentration of the dopant source solution is preferably from 0.01 mol / L to 15 mol / L, more preferably from 0.2 mol / L to 1 mol / L, for example, but not limited to any or both of the following values: 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L, 12 mol / L, 13 mol / L, 14 mol / L, and 15 mol / L.
[0018] In some embodiments, the lithium source is preferably at least one of lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate.
[0019] In some embodiments, the carbon source is preferably at least one selected from sucrose, glucose, citric acid, fructose, starch, maltose, cellulose, dextrin, lactose, oxalic acid, ascorbic acid, polypropylene, polyvinylpyrrolidone, polyethylene glycol, carbon black, carbon nanotubes, and graphene.
[0020] In some embodiments, the ionic conductive agent is at least one of NASICON-structured solid electrolyte and perovskite-type solid electrolyte, preferably at least one of LATP, LAGP, and LLTO.
[0021] The chemical formula of LATP is: Li 1+a Al a Ti 2-a-b M1 b (PO4)3, 0≤a≤0.5, 0≤b≤0.5, M1 is a dopant element, including at least one of Zn, Mg, Mn, Co, Ni, Cr, Al, Sc, In, Fe, Y, V, Nb, Ta, Sb, W, Mo, Ru, Ga, Ba, As, Hf, Ge, and Sn.
[0022] The chemical formula of LAGP is: Li 1+c Al c Ge 2-c-d M2 d (PO4)3, 0≤c≤0.5, 0≤d≤0.5, M2 is a doping element, including at least one of Zn, Mg, Mn, Co, Ni, Cr, Al, Sc, In, Fe, Y, V, Nb, Ta, Sb, W, Mo, Ru, Ga, Ba, As, Hf, Ge, and Sn.
[0023] The chemical formula of LLTO is: Li 3e La 2 / 3-e Ti f M3 1-f O3, 0<e<2 / 3, 0<f≤1, M3 is a doping element, including at least one of Nb, W, Ti, Hf, Ru, Mo, Nd, Ba, Ga, In, Ge, Sn, Sb, and Se.
[0024] In some embodiments, the polar organic solvent in the polar organic solvent solution is preferably at least one of alcohols, lipids, and ketoamides, more preferably dimethyl sulfoxide (DMSO).
[0025] In some embodiments, the concentration of the polar organic solvent solution is 0.01 mol / L to 15 mol / L, preferably 0.5 mol / L to 3 mol / L, for example, it may be, but is not limited to, any one of 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L, 12 mol / L, 13 mol / L, 14 mol / L, and 15 mol / L, or a range value of any two thereof.
[0026] As a preferred embodiment of the preparation method of the high-entropy lithium iron manganese phosphate composite positive electrode material according to the present invention, 0°C < T2-T1 ≤ 400°C; and / or 0°C < T3-T2 ≤ 400°C.
[0027] When the temperature difference between the second sintering stage and the first sintering stage is preferably within the above-mentioned range, it can not only better promote the formation of a porous framework during the first sintering stage, but also better promote the synergistic diffusion of multiple dopants into the manganese-iron sites during the second sintering stage. This allows different dopants to be uniformly embedded in the lattice, thereby achieving atomic-level homogenization of the high-entropy structure, forming a high-entropy solid solution, effectively suppressing Jahn-Teller distortion, stabilizing the olivine crystal structure, reducing volume changes and phase transformation stress during charging and discharging, and thus improving the cycle stability of the cathode material.
[0028] In some implementations, T2-T1 may be, but is not limited to, a range of any one or both of the following: 20°C, 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, and 400°C.
[0029] When the temperature difference between the third sintering stage and the second sintering stage is preferably within the above-mentioned range, on the one hand, it is beneficial to promote the synergistic diffusion of multiple dopants into the manganese-iron sites, so that different dopants can be uniformly embedded in the lattice to achieve atomic-level homogenization of the high-entropy structure; on the other hand, it can also ensure that the crystal particles grow fully before carbonization to form a nano-carbon layer, and at the same time, it can better exert the role of high-entropy elements in stabilizing the lattice and inhibiting abnormal grain growth.
[0030] In some implementations, T3-T2 may be, but is not limited to, a range of any one or both of the following: 20°C, 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, and 400°C.
[0031] In a preferred embodiment of the preparation method of the high-entropy lithium manganese iron phosphate composite cathode material of the present invention, 200℃≤T1≤400℃; and / or, 400℃≤T2≤600℃; and / or, 600℃≤T3≤800℃.
[0032] When the temperature of the first sintering stage is preferably within the above range, the generated gas is discharged in stages and slowly while the crystal water, organic matter and other volatile components in the raw materials are fully removed. This is more conducive to building a porous framework with gradient pore size inside the particles, so as to promote the full diffusion of doped elements in the second sintering stage.
[0033] In some implementations, T1 may be, but is not limited to, a range of any one or both of the following: 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, and 400°C.
[0034] When the temperature of the second sintering stage is preferably within the above range, it can not only better promote the recrystallization of grains and their gradual growth to form an olivine crystal structure, but also provide energy for various dopants to overcome the diffusion activation energy barrier, enabling them to be uniformly embedded in the lattice and achieve atomic-level homogenization of the high-entropy structure.
[0035] In some implementations, T2 may be, but is not limited to, a range of any one or both of the following: 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, and 600°C.
[0036] When the temperature of the third sintering stage is preferably within the above-mentioned range, it can not only provide migration energy for the point defects or low dislocations generated in the second sintering stage to promote their diffusion to the grain boundary or surface elimination, but also give full play to the role of high-entropy elements in stabilizing the crystal lattice and inhibiting abnormal grain growth at this temperature, thereby reducing the risk of abnormal grain growth. At the same time, the amorphous carbon formed by the carbon source in the first and second sintering stages can also undergo graphitization transformation and have better conductivity.
[0037] In some implementations, T3 may be, but is not limited to, a range of any one or both of the following: 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, and 800°C.
[0038] In a preferred embodiment of the preparation method of the high-entropy lithium manganese iron phosphate composite cathode material of the present invention, the sintering time of the first stage in step S3 is 2h to 24h, the sintering time of the second stage is 2h to 24h, and the sintering time of the third stage is 2h to 24h.
[0039] In some embodiments, the sintering time of the first stage may be, but is not limited to, any or both of the following: 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h.
[0040] In some embodiments, the second sintering time may be, but is not limited to, any or both of the following: 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h.
[0041] In some embodiments, the sintering time of the third stage may be, but is not limited to, any or any two of the following: 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, and 24h.
[0042] As a preferred embodiment of the preparation method of the high-entropy lithium manganese iron phosphate composite cathode material of the present invention, the temperature of the first co-precipitation reaction in step S1 is 25°C to 80°C. And / or, the temperature of the second coprecipitation reaction in step S2 is 25°C to 80°C.
[0043] The temperature of the first coprecipitation reaction mainly affects the nucleation, grain size and morphology of the phosphate precursor, as well as the uniformity of particle size and phase purity. The temperature of the second coprecipitation reaction mainly affects the uniformity of high-entropy multi-element co-precipitation, so as to achieve uniform doping without destroying the structure and morphology of the first coprecipitation product. When the two precipitation temperatures are preferably within the above range, the two can better work together to promote the high-entropy ions to penetrate into the particle to achieve bulk doping, while the surface has a complete high-entropy protective layer, thus taking into account the rate performance and cycle performance of the cathode material.
[0044] In some embodiments, the temperature of the first coprecipitation reaction in step S1 may be, but is not limited to, a range of any one or both of 25°C, 30°C, 35°C, 40°C, 45°C, 55°C, 60°C, 65°C, 70°C, 75°C, and 80°C.
[0045] In some embodiments, the temperature of the second coprecipitation reaction in step S2 may be, but is not limited to, any or both of the following ranges: 25°C, 30°C, 35°C, 40°C, 45°C, 55°C, 60°C, 65°C, 70°C, 75°C, and 80°C.
[0046] In a preferred embodiment of the preparation method of the high-entropy lithium manganese iron phosphate composite cathode material of the present invention, the average particle size of the phosphate precursor A in step S1 is 0.5 μm to 10 μm. And / or, the average particle size of the phosphate precursor B in step S2 is 0.8 μm to 20 μm.
[0047] The average particle size of phosphate precursor A mainly affects the internal ion diffusion, whether high entropy can enter the particle interior, tap density, precursor purity, sintered crystal growth, and particle skeleton stability of lithium manganese iron phosphate material. When the average particle size of phosphate precursor A is preferably within the above range, it can give lithium manganese iron phosphate better rate performance and cycle stability.
[0048] The average particle size of phosphate precursor B mainly affects the surface coating integrity, interfacial impedance, high entropy uniformity of multi-metals, and charge-discharge structure stability. When the average particle size of phosphate precursor B is preferably within the above range, it is more conducive to reducing the side reactions between lithium manganese iron phosphate and electrolyte and improving its long cycle life.
[0049] In some embodiments, the average particle size of the phosphate precursor A in step S1 may be, but is not limited to, a range of any one or both of the following: 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, and 10 μm.
[0050] In some embodiments, the average particle size of the phosphate precursor B in step S2 may be, but is not limited to, a range of any one or both of the following: 0.8 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, and 20 μm.
[0051] Secondly, the present invention provides a high-entropy lithium manganese iron phosphate composite cathode material, which is prepared by the above-mentioned preparation method.
[0052] In some embodiments, the average particle size of the high-entropy lithium manganese iron phosphate composite cathode material is preferably 1 μm to 15 μm.
[0053] In some embodiments, the average particle size of the high-entropy lithium manganese iron phosphate composite cathode material may be, but is not limited to, any or both of the following values: 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, and 15 μm.
[0054] As a preferred embodiment of the high-entropy lithium manganese iron phosphate composite cathode material of the present invention, the high-entropy lithium manganese iron phosphate composite cathode material includes a core and a coating layer located on at least a portion of the surface of the core, the coating layer comprising a carbon material and an ion-conducting agent.
[0055] In some implementations, the average particle size of the kernel is preferably from 0.5 μm to 20 μm.
[0056] In some implementations, the average particle size of the kernel may be, but is not limited to, a range of any or both of the following: 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm.
[0057] In some embodiments, the average thickness of the coating layer is preferably 2 nm to 100 nm.
[0058] In some embodiments, the average thickness of the coating layer may be, but is not limited to, a range of any or both of the following: 2 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, and 100 nm.
[0059] The average thickness of the coating layer in the high-entropy lithium manganese iron phosphate composite cathode material: The high-entropy lithium manganese iron phosphate composite cathode material was sliced using focused ion beam (FIB) and characterized by high-resolution transmission electron microscopy (HRTEM, model TalosF200X). Within the same selected area, five locations of the coating layer were randomly selected for measurement, and the arithmetic mean of the coating layer thickness at the five different locations was calculated to obtain the average thickness of the coating layer in the high-entropy lithium manganese iron phosphate composite cathode material.
[0060] As a preferred embodiment of the high-entropy lithium manganese iron phosphate composite cathode material of the present invention, based on the total mass of the high-entropy lithium manganese iron phosphate composite cathode material, the mass percentage of the carbon material is 1.2% to 2.2%, and the mass percentage of the ionic conductive agent is 0.5% to 1.5%.
[0061] In some embodiments, the mass percentage of carbon material in the high-entropy lithium manganese iron phosphate composite cathode material may be, but is not limited to, any one or any two of the following values: 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, and 2.2%.
[0062] The mass percentage of carbon material in the high-entropy lithium manganese iron phosphate composite cathode material was determined using a Dekai HCS infrared carbon and sulfur analyzer according to the standard GB / T 21023-2006 "Determination of total carbon and sulfur content in steel by infrared absorption method after combustion in a high-frequency induction furnace".
[0063] In some embodiments, the mass percentage of the ionic conductive agent in the high-entropy lithium manganese iron phosphate composite cathode material may be, but is not limited to, any one or any two of the following values: 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, and 1.5%.
[0064] Thirdly, the present invention provides an electrode comprising the aforementioned high-entropy lithium manganese iron phosphate composite cathode material.
[0065] Fourthly, the present invention provides a battery comprising the aforementioned electrode.
[0066] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention first constructs a phosphate precursor framework using iron, manganese, and phosphorus source solutions through a first liquid-phase precipitation process. This framework is then dispersed in a dispersant solution and mixed with the phosphorus and dopant source solutions for a second liquid-phase precipitation. This process allows multiple dopant sources to precipitate on the surface of the phosphate precursor framework, forming a high-entropy compound coating layer. This not only promotes the uniform distribution of dopant elements on the surface of the phosphate precursor framework at the atomic scale but also avoids compositional segregation caused by different solubility products of various dissimilar metal ions. Simultaneously, the first sintering stage removes water of crystallization, organic matter, and other volatile components from the raw materials, and allows some organic matter to initially decompose and generate gas. The gas is then released to form a porous framework, increasing the reaction area and providing channels for the full diffusion of subsequent dopant elements. The second sintering stage primarily involves increasing the temperature to accelerate the chemical reaction, causing the grains to recrystallize and gradually grow into an olivine crystal structure. This provides crucial energy and diffusion time for the various dopant elements, enabling them to uniformly embed into the crystal lattice and achieving atomic-level homogenization of the high-entropy structure. The third stage of sintering primarily improves crystallinity, repairs internal crystal defects, and enhances the intrinsic stability of the material. At this stage, the carbon source is fully carbonized, forming a uniform nano-carbon layer on the particle surface. This layer constructs a conductive network to compensate for the material's poor intrinsic conductivity and acts as a physical barrier to suppress side reactions. By combining two liquid-phase precipitation stages with three-stage gradient sintering, the high-entropy lithium manganese iron phosphate composite cathode material is endowed with excellent cycle stability and superior rate performance. Attached Figure Description
[0067] Figure 1 The image shows the XRD pattern of the high-entropy lithium manganese iron phosphate composite cathode material in Example 1. Figure 2This is a SEM image of the high-entropy lithium manganese iron phosphate composite cathode material in Example 1; Figure 3 The above is a charge-discharge curve of the high-entropy lithium manganese iron phosphate composite cathode material in Example 1 under the conditions of 2.5~4.3V / 0.1C. Detailed Implementation
[0068] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0069] Unless otherwise specified, all other materials and reagents used in the examples are commercially available.
[0070] <Testing Methods> 1. Average particle size: The average particle size was measured using a Malvern 3000 laser particle size analyzer.
[0071] 2. Compacted density: The compacted density was measured using a PRCD3100 powder conductivity and compacted density meter. During the test, the pressure was gradually increased from 20MPa to 220MPa (with a pressure holding time of 20MPa for 10s). The compacted density at 220MPa was then measured.
[0072] 3. Battery cycle test Under conditions of 25±2℃, charge-discharge cycle tests were conducted on coin cells using a battery testing system (Blue Electric series battery testing system). The test conditions were as follows: charge-discharge rates of 0.1C / 0.1C, 1C / 1C, and 8C / 8C, with a voltage range of 2.5V to 4.3V. One charge and one discharge cycle constituted one cycle. When the charge-discharge rate was 0.1C / 0.1C and the voltage range was 2.5V to 4.3V, the charge specific capacity and discharge specific capacity of the first cycle, as well as the charge-discharge efficiency (i.e., the coulombic efficiency of the first cycle) were recorded as formation data. When the charge-discharge rate was 1C / 1C and the voltage range was 2.5V to 4.3V, the capacity retention rate after 200 cycles was calculated as the discharge specific capacity of the 200th cycle / the discharge specific capacity of the 1st cycle × 100%. When the charge-discharge rate was 8C / 8C and the voltage range was 2.5V to 4.3V, the discharge specific capacity data of the first cycle was recorded as the discharge specific capacity at the 8C rate.
[0073] Example 1 <Preparation of High-Entropy Lithium Manganese Iron Phosphate Composite Cathode Material> (1) Dissolve 5.1 mol of manganese sulfate in water to obtain a manganese salt solution with a concentration of 2 mol / L; dissolve 3.4 mol of ferrous sulfate in water to obtain an iron salt solution with a concentration of 2 mol / L; dissolve 0.3 mol of zirconium sulfate, 0.3 mol of titanium sulfate, 0.15 mol of aluminum sulfate, 0.3 mol of niobium oxalate and 0.3 mol of lanthanum chloride in water to obtain a doping element source solution with a concentration of 0.5 mol / L; dissolve 11 mol of phosphoric acid in water to obtain a phosphorus source solution with a concentration of 2 mol / L; dissolve 25 mol of sodium hydroxide in water to obtain an alkaline solution with a concentration of 4 mol / L. The molar ratio of manganese in the manganese salt solution to iron in the iron salt solution is Mn:Fe = 6:4. The molar ratio of each metal element in the doped element source solution is Al:Ti:Zr:La:Nb = 1:1:1:1:1. The molar ratio of the total metal elements in the manganese salt solution, iron salt solution, and doped element source solution to the phosphorus elements in the phosphorus source solution is (Mn+Fe+Al+Ti+Zr+La+Nb):P = 1.0:1.1.
[0074] (2) The above manganese salt solution, phosphorus source solution and alkali solution are added to the reaction vessel in parallel flow. At the same time, the above iron salt solution is continuously added to the manganese salt solution so that the molar ratio of manganese to iron in the manganese-iron mixed solution entering the reaction vessel gradually changes from 1:0 to 0:1. By changing the addition rate of alkali solution, the pH of the reaction solution is adjusted to 8.0±0.1. The first co-precipitation reaction is carried out at 50°C for 2.5 h. After the reaction is completed, the solution is aged for 12 h to allow the metal ions in the solution to precipitate completely. The phosphate precursor A slurry is washed and filtered multiple times, placed in a vacuum drying oven and dried at 100°C for 12 h. The dried product is crushed to an average particle size of 500 nm to obtain phosphate precursor A.
[0075] (3) The above phosphate precursor A was added to 5L of polypropylene glycol polyol solution with a concentration of 1mol / L and dispersed to obtain a mixed slurry. Then, the above doping element source solution was added to the mixed slurry. At the same time, alkali solution and phosphorus source solution were added to control the pH of the slurry at 7±0.5. The second co-precipitation reaction was carried out at 45℃ for 1.5h. After the reaction was completed, the slurry was aged for 12h to allow the metal ions in the solution to precipitate completely. The phosphate precursor B slurry was washed and filtered multiple times and dried in a vacuum drying oven at 100℃ for 12h to obtain phosphate precursor B (average particle size of 4.5μm).
[0076] (4) The above-mentioned 1500g phosphate precursor B, 363.48g lithium carbonate, 88.25g glucose, 32.05g PEG, 5.82g graphene and 16.1g ion-conducting agent (Li) are added. 1.2 Al 0.2 Ti1.8 (PO4)3) was mixed evenly in 4 L of dimethyl sulfoxide (DMSO) solution (solvent: water, concentration: 2 mol / L), dried, and then placed in a graphite sagger and a box furnace. Under nitrogen atmosphere, the temperature was increased to 300 °C at a rate of 5 °C / min and sintered for 4 h (i.e., the first stage of sintering); then increased to 500 °C at a rate of 3 °C / min and sintered for 2 h (i.e., the second stage of sintering); and then increased to 750 °C at a rate of 1 °C / min and sintered for 7 h (i.e., the third stage of sintering). After cooling to room temperature, a high-entropy lithium manganese iron phosphate composite cathode material was obtained. The mass percentage of the ion-conducting agent in the high-entropy lithium manganese iron phosphate composite cathode material was 1%, and the mass percentage of the carbon material was 1.8%.
[0077] <Preparation of the positive electrode> The above-mentioned high-entropy lithium manganese iron phosphate composite cathode material, conductive carbon black (SP) and binder polyvinylidene fluoride (PVDF) were weighed at a mass ratio of 8:1:1, and ball-milled in a planetary ball mill for 2 hours using N-methylpyrrolidone (NMP) as solvent to prepare a cathode slurry. Then, the cathode slurry was coated onto an aluminum foil current collector, dried, and then rolled and punched into a cathode sheet. The sheet was then dried in a vacuum drying oven for 12 hours and then placed in a glove box under an inert gas protective atmosphere for later use.
[0078] <Preparation of Electrolyte> The electrolyte is 1 mol / L LiPF6, and the solvent is composed of ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) in a volume ratio of EC:DMC:DEC=1:1:1.
[0079] <Battery Manufacturing> The above-mentioned positive electrode, separator (polypropylene microporous membrane Celgard 2300), negative electrode (lithium metal sheet) and electrolyte are assembled into a CR2032 coin cell.
[0080] Example 2 Except for the first sintering temperature of 200℃ in step (4) of the <Preparation of High-Entropy Lithium Manganese Iron Phosphate Composite Cathode Material>, the rest is the same as in Example 1.
[0081] Example 3 Except for the first sintering temperature of 400℃ in step (4) of the <Preparation of High-Entropy Lithium Manganese Iron Phosphate Composite Cathode Material>, the rest is the same as in Example 1.
[0082] Example 4 Except for the second sintering temperature of 400℃ in step (4) of the <Preparation of high-entropy lithium manganese iron phosphate composite cathode material>, the rest is the same as in Example 1.
[0083] Example 5 Except for the second sintering temperature of 600℃ in step (4) of the <Preparation of High-Entropy Lithium Manganese Iron Phosphate Composite Cathode Material>, the rest is the same as in Example 1.
[0084] Example 6 Except for the third sintering temperature of 600℃ in step (4) of the <Preparation of High-Entropy Lithium Manganese Iron Phosphate Composite Cathode Material>, the rest is the same as in Example 1.
[0085] Example 7 Except for the first co-precipitation temperature of 25°C in step (2) and the second co-precipitation temperature of 80°C in step (3) of the <Preparation of High-Entropy Lithium Manganese Iron Phosphate Composite Cathode Material>, the rest is the same as in Example 1.
[0086] Example 8 Except for the first co-precipitation temperature of 80℃ in step (2) and the second co-precipitation temperature of 25℃ in step (3) of the <Preparation of High-Entropy Lithium Manganese Iron Phosphate Composite Cathode Material>, the rest is the same as in Example 1.
[0087] Example 9 In addition to step (1) of the <Preparation of High-Entropy Lithium Manganese Iron Phosphate Composite Cathode Material>, 0.3 mol of zirconium sulfate, 0.3 mol of titanium sulfate, 0.3 mol of copper sulfate, 0.3 mol of niobium oxalate and 0.3 mol of sodium tungstate are dissolved in water to obtain a doping element source solution with a concentration of 0.5 mol / L; The molar ratio of each metal element in the doped source solution is Cu:Ti:Zr:W:Nb=1:1:1:1:1. The molar ratio of the total metal elements in the manganese salt solution, iron salt solution and doped source solution to the phosphorus element in the phosphorus source solution is (Mn+Fe+Al+Ti+Zr+La+Nb):P=1.0:1.1. The rest is the same as in Example 1.
[0088] Comparative Example 1 Except for steps (2) and (3) of the <Preparation of High-Entropy Lithium Manganese Iron Phosphate Composite Cathode Material>, which are replaced by the following coprecipitation reaction (the specific steps are as follows), the rest are the same as in Example 1; The manganese salt solution, dopant source solution, phosphorus source solution, and alkaline solution were added to the reaction vessel in a parallel flow. Simultaneously, the iron salt solution was continuously added to the manganese salt solution, so that the molar ratio of manganese to iron in the manganese-iron mixed solution entering the reaction vessel gradually changed from 1:0 to 0:1. By changing the addition rate of the alkaline solution, the pH of the reaction solution was adjusted to 7.0±0.1. The co-precipitation reaction was carried out at room temperature (25℃) for 4 hours. After the reaction was completed, the solution was aged for 12 hours to obtain a phosphate precursor slurry. The phosphate precursor slurry was washed and filtered multiple times, and then dried in a vacuum drying oven at 100℃ for 12 hours to obtain the phosphate precursor.
[0089] Comparative Example 2 Except for omitting the third sintering stage in step (4) of the <Preparation of High-Entropy Lithium Manganese Iron Phosphate Composite Cathode Material>, and adjusting the sintering time of the first stage to 8h and the sintering time of the second stage to 5h, the rest is the same as in Example 1.
[0090] Comparative Example 3 Except for step (4) of the <Preparation of high-entropy lithium manganese iron phosphate composite cathode material> which omits the second sintering stage, and adjusts the first sintering time to 6h, the rest is the same as in Example 1.
[0091] Comparative Example 4 Except for step (4) of the <Preparation of high-entropy lithium manganese iron phosphate composite cathode material>, in which the first sintering stage is omitted and the second sintering time is adjusted to 6h, the rest is the same as in Example 1.
[0092] Comparative Example 5 Except for step (4) of the <Preparation of High-Entropy Lithium Manganese Iron Phosphate Composite Cathode Material>, in which only the third stage of sintering is performed, the rest is the same as in Example 1.
[0093] Comparative Example 6 Except for replacing the dimethyl sulfoxide solution in step (4) of the <Preparation of high-entropy lithium manganese iron phosphate composite cathode material> with water, the rest is the same as in Example 1.
[0094] The XRD and SEM images of the high-entropy lithium manganese iron phosphate composite cathode material in Example 1 are shown below. Figure 1 and Figure 2 As shown in Table 1, the cell parameters of the high-entropy lithium manganese iron phosphate composite cathode materials in Examples 1 and 2 and Comparative Example 6 are shown in Table 1.
[0095] Table 1 according to Figure 1 It can be seen that high-entropy element doping does not affect the structure of lithium manganese iron phosphate, and the fitted graph almost completely overlaps with the original graph, indicating a good fitting effect; Rp (graphic variance factor) and Rwp (weighted graphical variance factor) in Table 1 are both below 10%, indicating that the refined data is reliable, showing that high-entropy elements can reduce cell parameters, shorten the lithium-ion diffusion path (lithium ions mainly diffuse along the b-axis), improve the rate performance of the cathode material, and stabilize the crystal structure, thereby improving the cycle stability of the cathode material. In particular, the combination of polar organic solvents and high-entropy elements can further shorten the lithium-ion diffusion path; according to Figure 2 Further investigation revealed that high-entropy elements are evenly distributed, and the two co-precipitation processes can achieve atomic-level mixing, thus effectively avoiding element segregation problems.
[0096] Table 2 shows the compaction density of the high-entropy lithium manganese iron phosphate composite cathode materials in Examples 1-9 and Comparative Examples 1-6 and the corresponding battery performance.
[0097] Table 2 According to Table 2 and Figure 3 It can be seen that the compaction density of the high-entropy lithium manganese iron phosphate composite cathode material in Examples 1-9 reaches 2.30 g / cm³. 3 The corresponding batteries exhibit a 0.1C discharge specific capacity of 152.15~158.45 mAh / g, an 8C discharge specific capacity of 120.31~133.15 mAh / g, and a capacity retention rate of over 95% after 200 cycles at 1C. This indicates that the high-entropy lithium manganese iron phosphate composite cathode material prepared by the method of this invention possesses both good cycle stability and excellent rate performance.
[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a high-entropy lithium manganese iron phosphate composite cathode material, characterized in that, Includes the following steps: S1. Mix the iron salt solution, manganese salt solution and phosphorus source solution, carry out the first co-precipitation reaction, age and dry to obtain phosphate precursor A; S2. Mix the phosphate precursor A, dispersant solution, phosphorus source solution and dopant element source solution described in S1, and carry out a second co-precipitation reaction to obtain phosphate precursor B. S3. The phosphate precursor B, lithium source, carbon source, ionic conductive agent and polar organic solvent solution described in S2 are mixed and dried. The dried product is then subjected to first-stage sintering, second-stage sintering and third-stage sintering in an inert gas atmosphere to obtain a high-entropy lithium manganese iron phosphate composite cathode material. The ionic conductive agent is at least one of NASICON structure solid electrolyte and perovskite solid electrolyte. The doping element source solution in step S2 contains three or more doping elements; the doping elements include at least three of the following: Mg, Al, Ca, Ti, V, Cr, Ni, Co, Cu, Zn, Zr, Nb, Mo, Sn, Ta, W, Sb, and La. In step S3, the sintering temperature of the first stage is T1, the sintering temperature of the second stage is T2, and the sintering temperature of the third stage is T3. T1, T2, and T3 satisfy: T1 < T2 < T3. 230℃≤T1≤400℃; 400℃≤T2≤600℃; 600℃≤T3≤800℃.
2. The preparation method according to claim 1, characterized in that, The temperature of the first coprecipitation reaction in step S1 is 25°C to 80°C; And / or, the temperature of the second coprecipitation reaction in step S2 is 25°C to 80°C.
3. The preparation method according to claim 1, characterized in that, The average particle size of the phosphate precursor A in step S1 is 0.5 μm to 10 μm; And / or, the average particle size of the phosphate precursor B in step S2 is 0.8 μm to 20 μm.
Citation Information
Patent Citations
Lithium ferric manganese phosphate positive electrode material with iron and manganese elements in full-concentration gradient distribution and preparation method of lithium ferric manganese phosphate positive electrode material
CN114725340A
Lithium manganese iron phosphate positive electrode material for in-situ construction of high-entropy interface and preparation method of lithium manganese iron phosphate positive electrode material
CN119929764A
Carbon-doped high-entropy lithium manganese iron phosphate positive electrode material, preparation method thereof and battery
CN121964563A